Vibration sense and tarsal disintegration. - Klenerman, P; Hammond, C; Kulkarni, V; Mehta, J (1990)
The extent of loss of vibration and pressure sensations was assessed in 21 leprosy patients with disintegration of the tarsus. Feet which had and did not have tarsal disintegration both showed severe impairment of pressure sensation, but the loss of vibration sense was more severe in feet which had undergone the destructive process. It appears that loss of deep sensation is an important factor in the process of tarsal disintegration in feet which are already anaesthetic. Measurement of vibration sense using a biosthesiometer may be a valuable clinical test in the investigation and follow-up of the patient with the insensitive foot to identify those at risk of developing tarsal disintegration.